Artificial insemination of alpacas with semen collected by vaginal aspiration and by artificial vagina - Alarcón B., Virgilio (2012)
Semen from alpacas was collected by two methods: by aspiration from the female’s vagina following mating and with an artificial vagina. Semen was collected, evaluated and extended with Tris buffer, and then used in artificial insemination. Altogether 160 female alpacas with proven reproductive history and five males were used. Semen was collected by vaginal aspiration from 10 females using five males as semen donors; likewise, semen from the same males was collected with an artificial vagina twice a week 50 times. Volume, motility, spermatic concentration, live spermatozoa, viscosity and color was evaluated. Seminal characteristics of semen collected by aspiration and with an artificial vagina were: volume (3.6 and 1.5 mL), motility (73.4 and 69.0%), sperm concentration (75.2 and 80.3 million/mL), live spermatozoa (75.3 and 70.8%) respectively, with statistical difference between methods (p<0.05). Semen was mainly light red (80%) and showed a semi viscous consistency (90%) in semen collected by aspiration, and milky white (60%) and viscous (90%) from artificial vagina. Pregnancy diagnosis by ultrasonography 30 days after insemination was 55% (55/100) when using semen by aspiration and 48% (24/ 50) when using semen from artificial vagina (p<0.01). Semen collection from the vagina following mating yielded greater volume, better quality, and semi viscous consistency, and the percentage of pregnancy was higher than semen from artificial vagina.